Speech Acts: Richard Grayson and Matt Mullican - Wes Hill (UTS ePRESS, 2017)
Speech Acts: Richard Grayson and Matt Mullican illuminates the video-based practices of these two internationally acclaimed artists, who use the format of the monologue to construct and narrate hypothetical worlds. British artist Richard Grayson imbues vernacular culture with a sense of classicism, extracting layers of meaning from an array of subject matter, including scientific explanations, flash-mob videos, dinner party conversations and purposefully bad jokes. By contrast, American artist Matt Mullican​ examines the circularities of language, conducting performances under hypnosis to vacillate between primal and public speech. Who is it we are watching as Mullican performs in an hypnotic state? How do we interrogate and categorise what is being created? The book includes video excerpts of Mullican’s first ever performance under hypnosis in Australia (staged in collaboration with Sydney’s National Art School at the iconic Cell Block Theatre, a former nineteenth-century women’s prison) and a selection of Grayson’s scripted compositions, which combine political acuity with dry wit. Author Wes Hill, having curated Grayson and Mullican in a 2015 exhibition at UTS Gallery, unpacks them further in a fascinating essay on both artists, examining their obsessions with language, performance and the nature of interpretation, which arise in their works to engage and sometimes unsettle viewers.